Antigenic determinants and functional domains in core antigen and e antigen from hepatitis B virus. - Salfeld, J (1989)
The precore/core gene of hepatitis B virus directs the synthesis of two polypeptides, the 21-kilodalton subunit (p21c) forming the viral nucleocapsid (serologically defined as core antigen [HBcAg]) and a secreted processed protein (p17e, serologically defined as HBe antigen [HBeAg]). Although most of their primary amino acid sequences are identical, HBcAg and HBeAg display different antigenic properties that are widely used in hepatitis B virus diagnosis. To locate and to characterize the corresponding determinants, segments of the core gene were expressed in Escherichia coli and probed with a panel of polyclonal or monoclonal antibodies in radioimmunoassays or enzyme-linked immunosorbent assays, Western blots, and competition assays. Three distinct major determinants were characterized. The single conformational determinant responsible for HBc antigenicity in the assembled core (HBc) and a linear HBe-related determinant (HBe1) were both mapped to an overlapping hydrophilic sequence around amino acid 80; a second HBe determinant (HBe2) was assigned to a location in the vicinity of amino acid 138 but found to require for its antigenicity the intramolecular participation of the extended sequence between amino acids 10 and 140. It is postulated that HBcAg and HBeAg share common basic three-dimensional structure exposing the common linear determinant HBe1 but that they differ in the presentation of two conformational determinants that are either introduced (HBc) or masked (HBe2) in the assembled core. The simultaneous presentation of HBe1 and HBc, two distinctly different antigenic determinants with overlapping amino acid sequences, is interpreted to indicate the presence of slightly differently folded, stable conformational states of p21c in the hepatitis B virus nucleocapsid.